Literasi Matematika Siswa SMP dalam Menyelesaikan Soal Kontekstual Ditinjau dari Self-Efficacy - Ditasari Putri Andini; Pradnyo Wijayanti (Universitas Negeri Surabaya, 2026)
The low mathematics literacy scores of Indonesian students in the PISA international survey indicate their weak ability to understand and solve mathematics problems. One contributing factor is self-efficacy, which is students' belief in their own ability to solve problems. This study aims to describe the mathematics literacy of junior high school students with high and low self-efficacy in solving contextual problems. This study employed a descriptive qualitative approach involving two student subjects selected based on the results of a self-efficacy questionnaire and a mathematics ability test. The research instruments included contextual problems based on personal, social, and scientific contexts with first-order context and second-order context levels, with PISA competency levels 4–6, and semi-structured interview guidelines. The results showed that students with high self-efficacy formulated problems mathematics, by identifying problem information and representing information in mathematics form. Students applied problem-solving strategies appropriate to the problem context and interpreted and evaluated the results by linking them to the problem, although some information in the scientific context had not been considered. Meanwhile, students with low self-efficacy formulate problems, use incomplete solution strategies, and provide answers based on intuition or guesswork without using calculations. Evaluation of results is also often not linked to the context of the problem. These findings reinforce the important role of self-efficacy as an affective factor influencing students' mathematics literacy in solving contextual problems.